RESPON GURU DAN SISWA PADA PEMBELAJARAN TATAP MUKA DI MASA PANDEMI COVID 19 DI SD MUHAMMADIYAH PURWOKERTO - Sony Irianto (Universitas Muhammadiyah Surabaya, 2022)
Face-to-face learning (PTM) in Banyumas Regency, Central Java, started Wednesday (1/9/2021).Â This follows the decline in the status of the Implementation of Community Activity Restrictions (PPKM) from level 4 to 3. The Head of the Banyumas Education Authorities, Irawati, said that for the early stage, PTM would be tested in 54 schools.Â